A critical analysis of the relationship between political transformation and corruption - Cloete, Emmanuel Pringle (University of the Free State, 2013)
This thesis sets out to confirm the relationship between corruption and political transformation. The thesis commences by investigating different modes of political change with particular emphasis on the characteristics, nature and content of political transformation. With the relationship of the above phenomena being the focal point, the thesis extensively examines the concept of corruption by interrogating different definitions, its causes and consequences. It was also the aim of the study to context the role of ethics/morality as well as that of leadership within the relationship. The study applied a deductive and qualitative approach in exploring case studies in three African states prior to shifting focus to South Africa where both public sector departments as well as private sector experiences come under scrutiny. Apart from the broader South African environment, selected departments of the Eastern Provincial Government were also placed under the microscope as a continuation of the case-study approach. Drawing on the theories on the one hand and the case studies on the other, significant evidence could be found to categorically confirm the relationship between corruption and transformation. Overall this study is part of a growing body of research dealing with the effect of corruption in countries undergoing processes of political change. The study concludes by providing recommendations aimed at the development of an effective anti-corruption framework.
Thesis (Ph.D. (Programme in Governance and Political Transformation))--University of the Free State, 2013
Keywords: Political development; Political corruption -- South Africa; Corruption -- South Africa; South Africa -- Politics and government -- 20th century; South Africa -- Politics and government -- 21st century; Botswana; Nigeria; Zimbabwe; Political decay; Governance; Ethics; Modernisation; Transformation